1997
DOI: 10.1006/viro.1997.8574
|View full text |Cite
|
Sign up to set email alerts
|

Long Sequences in the 5′ Noncoding Region of Plum Pox Virus Are Not Necessary for Viral Infectivity but Contribute to Viral Competitiveness and Pathogenesis

Abstract: The 5'-terminal 31 nucleotides of the 146-nucleotides-long 5' noncoding region of plum pox potyvirus (PPV) are highly conserved in all the members of the Potyvirus genus. To map the sequences of the 5' noncoding region that are necessary in vivo for infectivity, we have constructed a nested set of substitution and deletion mutants. While we were not able to infect Nicotiana clevelandii plants with full-length PPV transcripts bearing mutations in the 5'-terminal 35 nucleotides of the viral genome, the deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…For example, plum pox virus mutants with a sequence deletion of nt 127-145 in the 5’UTR exhibited mild symptoms (Simon-Buela et al, 1997). Similarly, a seven nt insertion in the 5’UTR region in bean common mosaic virus resulted in more severe symptoms in asparagus bean (Zheng et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…For example, plum pox virus mutants with a sequence deletion of nt 127-145 in the 5’UTR exhibited mild symptoms (Simon-Buela et al, 1997). Similarly, a seven nt insertion in the 5’UTR region in bean common mosaic virus resulted in more severe symptoms in asparagus bean (Zheng et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…These include the CP gene of Alfalfa mosaic virus (AMV) [19], Cucumber mosaic virus (CMV) [20,21], Tobacco mosaic virus (TMV) [22], Turnip crinkle virus (TCV) [23], and Potato virus Y [24], the MP gene of Brome mosaic virus (BMV) [25]. Meanwhile, the involvement of 5 0 UTR for virulence, but dispensable for infection or replication, of AMV [26], Plum pox virus [27], and Tomato aspermy virus [28] has also been described. In addition, Fernandez et al [29] have reported that the 5 0 UTR of RNA-2 of Grapevine chrome mosaic virus, a member of Nepovirus, is triggered to induce severe necrotic symptoms on three Nicotiana species.…”
Section: Discussionmentioning
confidence: 99%
“…In the ihprolC-PP197 construct, the region of homology to PPV RNA genome spans the AUG initiation codon of the PPV polyprotein. It includes 13 nucleotides of the 5'UTR before the AUG initiation codon and the first 181 bp of the PPV polyprotein coding region, including sequences that are necessary for efficient translation [37] and part of the 18 nucleotide long sequence from base 127 to 145 reported to be required for efficient PPV-host interaction [38]. IhprolC-PP197 transgenic plants contain siRNAs of 23 and 25 bases homologous to the 197 bases of the PPV genome used in the hairpin construct.…”
Section: Discussionmentioning
confidence: 99%